Irrigation water quality and zinc on growth and yield of fenugreek (Trigonella foenumgraecum L.) - M R Choudhary, R K Jakhar, B L Yadav, (Journal of Spices and Aromatic Crops, 2013)
A pot experiment was carried out to find out the influence of different Residual Sodium Carbonate (RSC) water and zinc (Zn) levels on growth and yield of fenugreek. The study involved 12 treatment combinations of four RSC levels of irrigation water (W1=1, W2=2.5, W3=5.0 & W4=7.5 mmol L-1) and three Zn levels (Z0=control, Z10= 10 & Z20= 20 mg kg-1 soil). Results revealed that the plant height, number of pods plant-1, number of seeds pod-1, test weight, seed yield and straw yield of fenugreek significantly decreased with all levels of RSC water and increased with increasing levels of Zn. Thus, application of 20 mg kg-1 Zn under 2.5 mM L-1 of RSC water was found to be superior with respect to growth and yield of fenugreek.